Development of Student Worksheet Integrated by Differentiated-PjBL Model to Train Student Science Process Skills on Renewable Energy Material - Ellianawati, Ellianawati; Wahyu Wiji Lestari, Dina Ardilla; Subali, Bambang; Linuwih, Suharto; Syed Aris, Sharipah Ruzaina Aris (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This study is a research and development (R&D) to produce student worksheets that integrate the project-based learning model and a differentiated approach to train students' science process skills on renewable energy material. The development model used in this study is the ADDIE development model, namely analysis, design, development, implementation, and evaluation. This study aims to determine the feasibility and practicality of student worksheet products. Five expert validators conducted the product feasibility test, resulting in a score of 0.88 with valid criteria. Teachers and students carried out the product practicality test as users of student worksheets. The teacher's practicality test obtained an average score of 92.08% with very practical criteria, while the student's assessment obtained an average score of 86.95% with very practical criteria. Based on the feasibility and practical test results, the student worksheet products are feasible and practical for use in learning to train students' science process skills.